Thermal and structural analyses of extracted cellulose from olive husk. (2022) - Klaai, Lisa; Hammiche, Dalila; Boukerrou, Amar; Pandit, Vikram
Abstract: In the present work, Olive Husk (OH) waste is successfully utilized to produce cellulose by degreasing, eliminating hemicelluloses, and bleaching with a 74% yield. Fourier transform infrared spectroscopy (FTIR) analysis is used to characterize the structural properties of OH and cellulose samples. FTIR depicts the transmission peak 1745, 1375 and 1260 cm −1 due to wax, hemicellulose and lignin respectively. The thermal stability of OH and extracted cellulose was investigated by thermogravimetric analysis (TGA). The extracted cellulose had good thermal stability, the degradation temperature of the extracted cellulose.